Pengaruh Pemasaran Influencer dan Strategi Penetapan Harga Terhadap Proses Keputusan Pembelian Air Minum Dalam Kemasan (AMDK) - Afifa Nabila; Halimah Zahrah (Indonesia Economic Journal, 2026)
The packaged drinking water (AMDK) industry in Indonesia is facing increasingly intense competition due to rapid urbanization, high mobility among Generation Z, and the dominance of major brands such as Le Minerale. This condition encourages companies to optimize marketing strategies, particularly influencer marketing and pricing strategies, to influence young consumers’ purchase decision processes. This study aims to analyze the effect of influencer marketing and pricing strategy on t he purchase decision process of AMDK among Faculty of Economics and Business students aged 19–23 years. This research adopts a quantitative approach with a causal design and a cross-sectional survey method. Data were collected through questionnaires from 150 respondents selected using stratified random sampling and analyzed using multiple linear regression. The results indicate that influencer marketing has a positive and significant effect and serves as the dominant factor influencing the AMDK purchase decision process. Pricing strategy also has a positive and significant effect, although it plays a complementary role. Simultaneously, influencer marketing and pricing strategy significantly affect the purchase decision process, with a contribution of 47.9%. The study concludes that the synergy between influencer credibility and competitive price perception strengthens the AMDK purchase decision process among Generation Z consumers. These findings contribute theoretically to digital marketing and consumer behavior literature and provide practical implications for companies in designing effective marketing strategies targeting young consumers.